Effects of frequency and amount of stover mulching on soil nitrogen and the microbial functional guilds of the endosphere and rhizosphere - Song, Wenchen; Wang, Jing; Hou, Lei (Frontiers in Microbiology, 2022)
Stover mulching as a conservation and sustainable agricultural practice is beneficial for maintaining soil nitrogen (N) requirements and plant health. The microbial functional guilds of the root and rhizosphere are important factors in the soil nitrogen cycle. However, it is unclear how the frequency and amount of stover mulching influence microbial functional guilds in the root and rhizosphere. Therefore, we investigated the responses of the microbial functional guilds in the endosphere and rhizosphere to maize stover mulching amounts (0, 1/3, 2/3, and total stover mulching every year) and frequencies (once every three years and twice every three years) under 10-year no-till management. The bacterial functional guilds of nitrogen fixation, nitrification, and anaerobic nitrate oxidation displayed the significantly correlation with C/N, total nitrogen, NO3-, and NH4+. The fungal functional guilds of plant pathogens and saprotrophs showed significantly correlations with C/N, total nitrogen, and NO3-. Moreover, we found that bacterial guilds play a pivotal role in maintaining N requirements at the jointing stage, whereas root endophytic fungal guilds play a more important role than bacterial guilds in regulating plant health at the mature stage. The frequency and amount of stover mulching had significant effects on the microbial functional guilds in the root and rhizosphere. Our data suggest that stover mulch application twice every three years is the optimal mulching frequency because it yielded the lowest abundance of nitrifying and anaerobic nitrate-oxidising bacteria and the highest abundance of nitrogen-fixing bacteria at the jointing stage, as well as the lowest abundance of fungal plant pathogens in roots at the mature stage.